Correlation of structural and magnetic properties in a set of mononuclear lanthanide complexes - Comba, Peter; Klingeler, Rüdiger; Koo, Changhyun; Roberts, Asha E.; Wadepohl, Hubert; Werner, Johannes (Chemistry - a European journal, 2018)
The electronic and magnetic properties of a set of mononuclear terbium(III) and dysprosium(III) complexes with two tetradentate 1-hydroxy-pyridin-2-one (1,2-HOPO) ligands are reported. Two primary coordination geometries are observed, depending on the length of the linker between the 1,2-HOPO donor moieties and the resulting arrangements of the linker. Fine details of the magnetic circular dichroism (MCD) spectra of the dysprosium(III) complexes illustrate differences in the splitting of the J multiplets and allow for a thorough ligand field analysis. High frequency electron paramagnetic resonance (HF-EPR) studies of the terbium(III) complexes give insight into the composition of the ground states. Ab initio calculations are utilized to rationalize the experimental results and further illustrate the effect of the structural features on the electronic and magnetic properties of the different complexes.